O fracasso escolar e as dificuldades de aprendizagem: um estudo sobre a disseminação da relação entre fracasso escolar e as dificuldades de aprendizagem, veiculadas pela revista Nova Escola (2013 a 2019) - Costa, Luana Pereira da (2020)
School failure has been one of the most studied and investigated objects in educational research in the country, as it has been expressed by different forms of selection and classification of students, it has become a constitutive mark of the Brazilian school system. Although the most profound causes of school failure are of socio-political origin, immediately it manifests itself mainly through academic learning difficulties, revealed by the low levels of student achievement, especially those coming from public schools, one of the explanations disseminated for what we conceptualize as the pathologization of school failure. Thus, this investigation aimed to analyze the processes of disseminating the relationship between school failure and learning difficulties, as the specialized literature has indicated that a good portion of the students who now fail at school, have been inadequately characterized as a carrier of difficulties. To this end, we use the Nova Escola Magazine as a corpus of analysis, a journal with wide national distribution, covering a variety of subjects related to Education, published in the form of articles, interviews, experience reports, activity suggestions, lesson plans and ready projects. The Journal was launched in 1986, a period in which the country sought to consolidate the democratization of the country, with the aim of updating and informing the Brazilian professor. The periodical was for more than 30 years in Grupo Abril, founded in 1950 by Victor Civita, and became one of the largest and most influential communication groups in Latin America and consolidated itself as the largest publisher of commercial magazines in the country. Therefore, considering the Nova Escola Magazine as a channel for the dissemination of pedagogical and teaching knowledge, favoring the socialization of educational experiences and fostering the exchange between educators, as a means of communication that is part of the cultural industry, which propagates through its content, the ideas of its producers and consumers, we elaborated the following questions: Which expressions of school failure were most disseminated by Nova Escola magazine, in the period between 2013 to 2019? How were learning difficulties addressed during this period? Thus, although edited and distributed since 1986, for this research we stipulate a time frame of six (6) years of publications of the Journal, between the years 2013 to 2019, a period in which we found the entire collection of the Magazine made available digitally , a point that favored access to all content and enabled a comparison based on the number of publications on both listed themes, School Failure and Learning Difficulties, and made a total of 70 editions. The data collection procedure took place through the descriptors: Learning Difficulties, whose 138 publications were found and School Failure, where we came across 149 subjects, based on this premise, we organized seven (7) categories of analysis. The collected data were included in an Excel spreadsheet that, when finalized, was exported to the Sphinx iQ2 statistical treatment software, whose methodology is expressed in the body of chapter 2